Analysis of Numeracy Literacy Abilities in Solving Minimum Competency Assessment Tasks Based On Students' Cognitive Styles - Diah Tri Muharini Muharini; Iwit Prihatin; Wandra Irvandi (Riemann: Research of Mathematics and Mathematics Education, 2025)
This study aims to analyze students' numeracy literacy skills in solving Minimum Competency Assessment (AKM) problems based on their cognitive styles, focusing on reflective and impulsive cognitive styles. The research employs a qualitative descriptive method, enabling an in-depth exploration of students' numeracy literacy abilities at MTs Negeri 01 Pontianak. Data collection techniques include AKM tests, the Matching Familiar Figure Test (MFFT), and interviews. The findings indicate that a reflective cognitive style significantly influences students' ability to solve AKM problems. Students with high numeracy literacy skills meet all numeracy literacy indicators. Meanwhile, students with moderate numeracy literacy skills fail to meet one indicator, namely interpreting. Students with low numeracy literacy skills can only fulfill one indicator, namely formulating. On the other hand, the impulsive cognitive style also affects how students approach AKM problems. Students with high numeracy literacy skills fulfill all numeracy literacy indicators. In contrast, students with moderate numeracy literacy skills meet only one indicator, namely applying. Students with low numeracy literacy skills fail to meet any of the indicators. This research highlights the importance of developing learning strategies that consider students' cognitive styles to enhance their numeracy literacy skills.